2021
DOI: 10.23917/ijolae.v3i3.15151
|View full text |Cite
|
Sign up to set email alerts
|

Learning Patterns during the Disruptive Situation in Informal Education: Parents’ Efforts and Challenges in the Adjustment of Progressive Learning

Abstract: This study investigates informal learning during the Covid-19 pandemic in Indonesia. Distant learning during the Covid 19 pandemic affects all aspects of education, including parents’ roles that switch to be teachers at home. This condition enables new learning patterns in order to offer children learning opportunities in their home. This study employs a qualitative approach with ethnographic design. The data collection techniques used an open observation guide which was examined for its validity using face an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Gita felt that her mother could not understand her. Good parents must adapt to their children because parents who cannot adapt well will cause conflicts with their children [55]. She found it difficult to listen to her mother's words because she always had different opinions from her mother since childhood.…”
Section: Stubbornnessmentioning
confidence: 99%
“…Gita felt that her mother could not understand her. Good parents must adapt to their children because parents who cannot adapt well will cause conflicts with their children [55]. She found it difficult to listen to her mother's words because she always had different opinions from her mother since childhood.…”
Section: Stubbornnessmentioning
confidence: 99%
“…Dari hasil penelitian di atas, dapat disimpulkan bahwa program kerja KKN-Dik dengan sistem pemberdayaan kelompok bela-jar perlu dilaksanakan guna meningkatkan pemahaman siswa kelas 6 terhadap materi ajar. Kegiatan KKN-Dik mengacu pada kegiatan yang berbasis masalah pada setiap program kerja yang dilaksanakan pada masyarakat pendidikan setempat, sehingga sangat penting untuk dilaksanakan (Djamdjuri, et al, 2018;Ratih et al, 2021). Dengan program kerja pemberdayaan kelom-pok belajar home visit dengan sistem four day four places sebagai bentuk pendalaman materi kelas 6 SD Muhammadiyah Program Khusus Tumang, diharapkan dapat meningkatkan kompetensi dalam aspek pengetahuan dan keterampilan.…”
Section: Informasi Artikel Abstrakunclassified
“…observed that in the modern era of technology, both teachers and students relied excessively on technology for achieving the goals of successful learning [7]. Moreover, the introduction of contemporary teaching pedagogies like blended learning [8], [9] and flipped learning (classrooms) [10], [11] in education has revealed persuasive evidence of progressive developments in the area of education [12].…”
Section: Introductionmentioning
confidence: 99%